Hormonal Contraception and Bone Health in Adolescents - Bachrach, Laura K. (Frontiers in Endocrinology, 2020)
Hormonal contraception is prescribed commonly to adolescents for myriad indications from pregnancy prevention to treatment for acne, hirsutism or dysmenorrhea. Although use of these hormones generally has no effect or benefits bone health in mature premenopausal women, the same may not be true for adolescents. The teen years are a critical period for acquiring peak bone strength. Sex hormones, growth hormone, and insulin-like growth factors (IGFs) interact to modulate the changes in bone size, geometry, mineral content, and microarchitecture that determine skeletal strength. Combined oral contraceptives (COCs) and intramuscular depo medroxyprogesterone (DMPA) can compromise the expected gains in adolescence by altering estrogen and IGF concentrations. Use of these medications has been associated with slower accrual of bone mineral density (BMD) and increased fracture risk in some studies. Far less is known about the skeletal effects of the newer long acting reversible contraceptives (LARCs). This review takes a critical look at the gaps in current knowledge of the skeletal effects of COCs, DMPA, and LARCs and underscores the need for additional research.